Racial implicit bias among obstetricians and midwives, and information on Down syndrome screening. (20th October 2021) - Azria, E; Rousseau, A; Anselem, O; Bonnet, MP; Deneux, C; Sauvegrain, P; Richetin, J
Abstract: Background and objectives: Previous studies showed disparities in prenatal screening for Down syndrome according to the maternal place of birth. Among the factors that might be involved in these differences, social cognition offers the concept of implicit bias (IB) used to describe the fact of having attitudes towards people or associating stereotypes with them without necessarily conscious knowledge. In line with theoretical and empirical contributions in social psychology that postulate and demonstrate the role of automatic processes in determining behavior, IBs often predict how individuals behave more accurately than conscious values. The existence of IB among health professionals has been demonstrated in emergency care or pain management. To our knowledge, no study of IB has been conducted in Europe, nor in the field of perinatal care. Thus, our objectives were to test for IBs towards African women in terms of evaluation (negative bias) and strength (positive bias) among perinatal health professionals and test whether these IBs predicted treatment recommendations toward African vs. French patients. Methods: Through online data collection, 887 perinatal care practicians (obstetrician-gynecologists, midwives) answered a series of case vignettes depicting African vs. French patients, with one specific to a Down syndrome screening situation. Then, participants completed two Implicit Association Tests to assess valence and strength IBs toward African vs. French women. Results: 81.3% of the sample showed an implicit evaluative preference for French over African women, and 60.2% had an implicit perception of African women as stronger than French. However, decision toward Down syndrome screening were not influenced by the patient's origin nor by the healthcare professional implicit bias. Conclusions: Perinatal practicians seem to have implicit biases toward African women, but the way they provide information regarding Down Syndrome screening is not affected.